Alex Rider. Skeleton Key - Johnston, Antony; Horowitz, Anthony, 1955- (Philomel Books, 2009)
When MI6 calls Alex Rider into action once again, Alex is sent to Skeleton Key, an island near Cuba, to combat the evil machinations of a Russian known as General Sarov.